EDUCATIONAL TECHNOLOGIES IN TRAINING FUTURE MANAGERS - Oksana Stupak (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The introduction of educational technologies, which are developing at a rapid pace, requires professionalism and readiness of managers to implement the latest information technologies. Therefore, the use of electronic resources in the educational process in higher education can contribute both to developing professional skills and gaining the experience of using online environment. Purpose of the paper is to analyse the electronic educational resources and describe the process of implementing online games in future managers' training. Method. The survey on the use of electronic resources in the learning process is conducted among 50 Master students who study full-time and part-time to gain the speciality "Management". Online courses and tests developed with the help of electronic resources are the most popular among the students, while WebQuest, quizzes and online games are used only by a small number of respondents. The survey shows that the use of electronic resources is insufficient in future managers' training. Findings. Within the course "Information Systems and Technologies in Management of Organisation" an interactive online game on online platform Goosechase was developed. This resource can give the opportunity to fulfil assignments in the course by displaying photos and video materials, which contribute to involving participants into а team game and developing future managers' key competences in the course. Implications for research and practice. The results of this study allow to conclude that training of students is successful if an online game is used which can be adapted for various specialities and courses.